Effect of different landing actions on knee joint biomechanics of female college athletes: Based on opensim simulation - Chen, Liang; Jiang, Ziang; Yang, Chen; Cheng, Rongshan; Zheng, Size; Qian, Jingguang (Frontiers in Bioengineering and Biotechnology, 2022)
Background: The anterior cruciate ligament (ACL) is one of the most injurious parts of the knee in the biomechanical environment during landing actions. The purpose of this study was to compare the lower limb differences in movement patterns, muscle forces and ACL forces during drop landing (DL), drop vertical jump (DVJ) and forward vertical jump (FVJ). Methods: Eleven basketball and volleyball female college athletes (Division II and I) were recruited. Landing actions of DL, DVJ and FVJ, kinematics and dynamics data were collected synchronously using a motion capture system. OpenSim was used to calculate the ACL load, knee joint angle and moment, and muscle force. Results: At initial contact, different landing movements influenced knee flexion angle; DL action was significantly less than FVJ action (p = 0.046). Different landing actions affected quadriceps femoris forces; FVJ was significantly greater than DL and DVJ actions (p = 0.002 and p = 0.037, respectively). However, different landing movements had no significant effects on other variables (knee extension moment, knee valgus angle and moment, hamstring and gastrocnemius muscle forces, and ACL forces) (p > 0.050). Conclusion: There was no significant difference in the knee valgus, knee valgus moment, and the ACL forces between the three landing actions. However, knee flexion angle, knee extension moments sagittal factors, and quadriceps and gastrocnemius forces are critical factors for ACL injury. The DL action had a significantly smaller knee flexion angle, which may increase the risk of ACL injury, and not recommended to assess the risk of ACL injuries. The FVJ action had a larger knee flexion angle and higher quadriceps femoris forces that were more in line with daily training and competition needs. Therefore, it is recommended to use FVJ action in future studies on risk assessment of ACL injuries and injury prevention in female college athletes.